Caracterização da problemática da acessibilidade urbana com base no valor do tempo percebido pelos usuários - Souza, Hélio Henrique Holanda de (2018)
Understand the problems in the relation between transportation, the use of soil and activities is essential in the development of appropriate solutions in urban mobility and accessibility. The effort to characterize and diagnose these problems should be a relevant part of the transportation planning process focusing on accessibility, requiring a better reflection of the measures which represent the spatial separations between the activities and the people willing to access them. In this way, urban accessibility issues became important and should be better analyzed. Therefore, issues that concern research about the value of time and its modeling in the planning process, as well as the suitability of indicators based in that modeling to characterize accessibility issues in the user’s perspective become relevant. Based on the analysis and discussion concerning these issues, a methodology proposal was developed characterizing the problem of urban accessibility, using logsum indicators. This methodology incorporates the perception of the users and regards the inefficiency of the transport system´s supply and a typology of accessibility problems. The application of the proposed method was verified with data from the Public Transport system of the Metropolitan Region of Fortaleza, enabling the space characterization of the different accessibility between zones and social groups, as well as benefits with the inclusion of new mode of transport. The use of behavioral models in the analytical effort is the main contribution of this thesis for better comprehension of the problems concerning the accessibility under the equity principle.